Retrieval of hourly PM2.5 using top-of-atmosphere reflectance from geostationary ocean color imagers I and II. (15th April 2023) - Choi, Hyunyoung; Park, Seonyoung; Kang, Yoojin; Im, Jungho; Song, Sanghyeon
Abstract: To produce real-time ground-level information on particulate matter with a diameter equal to or less than 2.5 μm (PM2.5 ), many studies have explored the applicability of satellite data, particularly aerosol optical depth (AOD). However, many of the techniques used are computationally demanding; to overcome these challenges, machine learning(ML)-based research has been on the rise. Here, we used ML techniques to directly estimate ground-level PM2.5 concentrations over South Korea using top-of-atmosphere (TOA) reflectance from the Geostationary Ocean Color Imager I (GOCI-I) and its next generation GOCI-II with improved spatial, spectral, and temporal resolutions. Three ML techniques were used to estimate ground-level PM2.5 concentrations: random forest, light gradient boosting machine (LGBM), and artificial neural network. Three schemes were examined based on the input feature composition of the GOCI spectral bands: scheme 1 using all GOCI-I bands, scheme 2 using only GOCI-II bands that overlap with GOCI-I bands, and scheme 3 using all GOCI-II bands. The results showed that LGBM performed better than the other ML models. GOCI–II–based schemes 2 and 3 (determination of coefficient (R 2 ) = 0.85 and 0.85 and root-mean-square-error (RMSE) = 7.69 and 7.82 μg/m 3, respectively) performed slightly better than GOCI-I-based scheme 1 (R 2 = 0.83 and RMSE = 8.49 μg/m 3 ). In particular, TOA reflectance at a new channel (380 nm) of GOCI-II was identified as the most contributing variable, given its high sensitivity to aerosols. The long-term estimation of PM2.5 concentrations using the proposed models was examined for ground stations located in two major cities. GOCI–II–based models produced a more detailed spatial distribution of PM2.5 concentrations owing to their higher spatial resolution (i.e., 250 m). The use of TOA reflectance data, instead of AOD and other aerosol products commonly used in previous studies, reduced the missing rate of the estimated ground-level PM2.5 concentrations by up to 50%. Our results indicate that the proposed approach using TOA reflectance data from geostationary satellite sensors has great potential for estimating ground-level PM2.5 concentrations for operational purposes. Graphical abstract: Image 1 Highlights: Hourly PM2.5 estimation was conducted directly using TOA reflectance from GOCI series. TOA-based PM2.5 estimation greatly reduced missing rates compared to AOD-based one. New spectral bands of GOCI-II contributed significantly to PM2.5 estimation. Continuity of GOCI-I/II models enabled stable long-term monitoring of PM2.5 .